Selective Anterior Lumbar Interbody Fusion for Low Back Pain Associated With Degenerative Disc Disease Versus Nonsurgical Management. Issue 19 (1st October 2018) - Kleimeyer, John P.; Cheng, Ivan; Alamin, Todd F.; Hu, Serena S.; Cha, Thomas; Yanamadala, Vijay; Wood, Kirkham B.
Abstract : Study Design: This is a retrospective cohort study. Objective: To evaluate the long-term outcomes of selective one- to two-level anterior lumbar interbody fusions (ALIFs) in the lower lumbar spine versus continued nonsurgical management. Summary of Background Data: Low back pain associated with lumbar intervertebral disc degeneration is common with substantial economic impact, yet treatment remains controversial. Surgical fusion has previously provided mixed results with limited durable improvement of pain and function. Methods: Seventy-five patients with one or two levels of symptomatic Pfirrmann grades 3 to 5 disc degeneration from L3-S1 were identified. All patients had failed at least 6 months of nonsurgical treatment. Forty-two patients underwent one- or two-level ALIFs; 33 continued multimodal nonsurgical care. Patients were evaluated radiographically and the visual analog pain scale (VAS), Oswestry Disability Index (ODI), EuroQol five dimensions (EQ-5D), and Patient-Reported Outcomes Measurement Information System scores for pain interference, pain intensity, and anxiety. As-treated analysis was performed to evaluate outcomes at a mean follow-up of 7.4 years (range: 2.5–12). Results: There were no differences in pretreatment demographics or nonsurgical therapy utilization between study arms. At final follow-up, the surgical arm demonstrated lower VAS, ODI, EQ-5D, and Patient-Reported Outcomes Measurement Information System pain intensity scores versus the nonsurgical arm. VAS and ODI scores improved 52.3% and 51.1% in the surgical arm, respectively, versus 15.8% and −0.8% in the nonsurgical arm. Single-level fusions demonstrated improved outcomes versus two-level fusions. The pseudarthrosis rate was 6.5%, with one patient undergoing reoperation. Asymptomatic adjacent segment degeneration was identified in 11.9% of patients. Conclusion: Selective ALIF limited to one or two levels in the lower lumbar spine provided improved pain and function when compared with continued nonsurgical care. ALIF may be a safe and effective treatment for low back pain associated with disc degeneration in select patients who fail nonsurgical management. Level of Evidence: 3